METHODOLOGICAL PERFORMANCE EVALUATION BY TEACHERS IN PRESCHOOL EDUCATIONAL INTITUTIONS - Natalia Anatolyevna Stepanova; Lilia Nailevna Sannikova; Nataliya Ivanovna Levshina; Svetlana Nikolayevna Yurevich; Galina Vyacheslavovna Ilyina (International Journal of Cognitive Research in Science, Engineering and Education, 2018)
The article describes a technology of teachers’ assessment of methodological performance as an aspect of preschool educational establishment management. Theoretical methods have been the major problem research methods: analysis of normative legal documents; theoretical and methodological analysis; system analysis; design approach; empirical methods: ascertaining experiment, questionnaire survey, interviews with preschool teachers. The authors have determined a theoretical and methodological framework for the study of the problem of effective methodological performance evaluation by teachers in preschool educational institutions; principles of implementing this technology have been proposed. In addition to the methodological performance evaluation technology by teachers, which includes research and monitoring stages and a decision-making stage, the authors have developed implementation charts for assessing methodological performance by teachers in preschool educational establishments and defined the criterion and level characteristics of methodological performance. Carrying out the procedure for assessing methodological performance in a PEI will ensure support for the organization’s processes, as well as facilitate a transfer of the organization from a merely functioning state to the state of dynamic development.